Graduate Literacy Students' Reading Completion - Linda Rak; Kathleen Olmstead; Jie Zhang; Carole Pelttari (Brock University, 2021)
Course reading completion enhances student learning and helps deepen students' thinking about concepts and ideas presented in class.  To better understand the students' reading completion and the factors which impact course reading compliance, the researchers engaged in an action research with 434 students enrolled in six graduate level literacy courses, or 28 classes, over nine years from 2009 through 2017.  The researchers shared the results and discussed recommendations to Literacy instructors for course improvement.